2018
DOI: 10.1111/ajo.12836
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of women recommended a laparoscopy for chronic pelvic pain at a tertiary institution

Abstract: The characteristics of women booked for surgery were in keeping with the features evidence suggests increases the risk of pathology. There were some discrepancies between patient characteristics elicited in the questionnaires and those indicated by gynaecologists to influence their decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Several studies have demonstrated a recurrence of pain within 12–18 months, with many young women then undergoing repeat surgical procedure(s) 9,10 . Predictors for repeat laparoscopy for pelvic pain include younger age and previous pelvic laparoscopy 11,12 . A placebo effect of up to 30% has been reported in the literature, whereas up to 20% of women describe no improvement in symptoms 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated a recurrence of pain within 12–18 months, with many young women then undergoing repeat surgical procedure(s) 9,10 . Predictors for repeat laparoscopy for pelvic pain include younger age and previous pelvic laparoscopy 11,12 . A placebo effect of up to 30% has been reported in the literature, whereas up to 20% of women describe no improvement in symptoms 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous PPP publication reporting on the characteristics of women who underwent laparoscopy in the first 211 participants, demonstrated that only severe dysmenorrhoea predicted surgery 20 . Analysis of data by gynaecology unit was not performed to avoid potentially influencing clinician behaviour in the remainder of the study.…”
Section: Discussionmentioning
confidence: 99%
“…10 Women with CPP are more likely to be offered surgery if they experience factors increasing the likelihood of pathology such as severe and prolonged pain. 11 However, the finding of endometriosis does not correlate with any specific pain symptoms, 10 or any cluster of symptoms, 12 and the extent of endometriosis does not correlate with severity of symptoms. 13 Furthermore with diverse symptomatology, there are often significant delays between first presentation and eventual diagnosis of endometriosis.…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 93%
“…This time period was chosen to encompass the study time of the 'Persistent Pelvic Pain' study which explores the outcomes of women referred for pelvic pain as previously published. 10,11 Women who had multiple surgeries during the study period (n = 25), were only included once. Patients without formal referrals in their file were excluded from the study (n = 8), as were women who had a hysterectomy prior to their initial consult (n = 2).…”
Section: Inclusion Criteria Included Age Between 18 and 50 Years And ...mentioning
confidence: 99%
See 1 more Smart Citation